Book Review: Natural Resources and Conflict in Africa: The Tragedy of Endowment - Nurudeen Akinyemi (Journal of Global Initiatives, 2010)
Reviews the book Natural Resources and Conflict in Africa: The Tragedy of Endowment, by Abiodun Alao. Published by University of Rochester Press, 2007.